Acute and long-term effects of adolescent methylphenidate on decision-making and dopamine receptor mRNA expression in the orbitofrontal cortex - Amodeo, Leslie R. (Behav Brain Res, 2017)
Though commonly used as a treatment for ADHD, the psychostimulant methylphenidate (MPH) is also misused and abused in adolescence in both clinical and general populations. Although MPH acts via pathways activated by other drugs of abuse, the short- and long-term effects of MPH on reward processing in learning and decision-making are not clearly understood. We examined the effect of adolescent MPH treatment on a battery of reward-directed behaviors both in adolescence during its administration and in adulthood after its discontinuation. We further measured whether MPH had lasting effects on dopamine receptor mRNA expression in orbitofrontal cortex (OFC) that may correspond with behavior. Long-Evans rats were injected with MPH (0, 1, 2.5, or 5 mg/kg IP) twice daily from middle to late adolescence (PD38-57). During adolescence, the high dose of MPH reduced preference for large rewards in a Reward Magnitude Discrimination task, but did not affect preference for smaller-sooner rewards in a Delay Discounting task. In adulthood, after discontinuation of MPH, animals previously treated with the moderate dose of MPH showed improved acquisition, but not reversal, in a Reversal Learning task. MPH exposure did not increase preference for large-risky rewards in a Risk task in adulthood. We then quantified mRNA expression of D1, D2, and D3 receptors in the OFC using qPCR. MPH increased mRNA expression of dopamine D3 receptor subtype, but not D1 or D2. Overall, these results indicate that MPH has both immediate and lasting effects on reward-dependent learning and decisions, as well as dopaminergic function in rodents.